Descripción del proceso de curtiembre enfocados en la reutilización y reciclaje de los residuos sólidos y líquidos en el tratamiento de curtiembre. - Chaglla Masaquiza, Alex Mauricio (2025)
his study proposes a comprehensive strategy for the reuse of solid and liquid waste generated by tanneries to mitigate the environmental pollution associated with this type of industry. Tanneries are responsible for a high volume of waste, both solid (such as leather scraps, leather dust, and packaging materials) and liquid (such as wastewater loaded with toxic chemicals). If not properly managed, these wastes pose a significant risk to the environment and public health. The research focuses on two key areas: the reuse of solid waste through recycling processes and the treatment of liquid wastes. The proposal also includes the implementation of a waste management system that ensures the proper segregation of different types of it and their subsequent reuse. Various available technologies are analyzed, and pilot tests are conducted in a tannery to evaluate the efficiency of the proposed processes. Furthermore, an environmental impact study is carried out to measure the reduction in pollutant load in wastewater and the decrease in the tannery’s ecological footprint. This work demonstrates that the reuse of solid and liquid waste from tanneries is not only a viable solution for reducing pollution but also offers opportunities to generate economic value and promote sustainability within the tanning industry. Adopting these practices contributes to environmental conservation and represents a significant step toward a more efficient and responsible circular economy.